Keragaman Genetik Karakter Kuantitatif Pada Tanaman Cabai Rawit - Kulakat, Kartika A; Kesaulya, Henry; Hehanussa, Meitty L (Universitas Pattimura, 2024)
The production of cayenne pepper is one of the leading national horticultural commodities; the Central Statistics Agency (BPS) cayenne pepper production of 1.39 million tonnes in 2021; the number fell by 8.09% compared to the previous year of 1.5 million tonnes. Chilli production can be increased through plant programs. This and chili plants in Buru were conducted on Buru Island. In January – June 2023. This used a one-factor Randomise Design. The factors were four local varieties (accession Buru 1, Buru 2, Buru 3 dan accession Halmahera) and six improved varieties (variety Rama, Pelita, Dewata, Mahameru, Dompu, and variety Sret 3). 30 units of 20 plants in 3 sample plants in each plot. The results (1) 11 showed a high value of and high expectation in pepper growing, (2) The cayenne pepper varieties production quantitative, fruit weight, plant fruit weight, and number of fruit on the tree.